Go Global - Nguyen, Phi Van (Văn hóa - Văn nghệ, 2018)
Go Global provides an initial introduction to the concept, history and present-day status of business format franchising in Chapter 1, to ensure the reader has a foundational understanding before the immersion into the key subject matter. Thereafter the book jumps right into the key subject matter and has 9 solid chapters of information, examples and checklists ideally suited in both content and chronology to help an entrepreneur or small business owner to understand the type of self-analysis and other key considerations that are critical to successfully transitioning their business to a successful franchise. Go Global concludes with insights into the status of today’s quickly evolving business and industry environment and the leveling of the global marketplace as a result of connectivity and technology and the growing and positive socio-economic impact of franchising globally and shows that Phi already has her eye on what the future of franchising is going to look like.